2014
DOI: 10.1093/trstmh/tru013
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and risk factors of soil-transmitted helminth infection in Nepal

Abstract: STH infection was associated with individual hygiene behavior, but not with nutritional status or socio-demographic characteristics. Health policy focusing on changing individual hygiene behaviors might be useful in addressing STH infection in Nepal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
1
20
1
1
Order By: Relevance
“…This might be due to the difference in skin texture and size of the foot which help the infective larva to easily access and penetrate in podoconiosis patients. Similarly the prevalence of intestinal helminthes among healthy participants was greater than the study conducted in Wolaita (33.1%) [10],Hawassa (48.8%) [17], Jimma (46.63%) [18], Daressalaam urban Tanzania (25.9%) [19], Kenya (0.2%) [20], and Nepal (9.1%) [21]. The difference might be due to geographical and socioeconomic variation because different areas may have difference in sanitation practice, warm and moist soils which facilitate the transmission and development of parasite ova and larva.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This might be due to the difference in skin texture and size of the foot which help the infective larva to easily access and penetrate in podoconiosis patients. Similarly the prevalence of intestinal helminthes among healthy participants was greater than the study conducted in Wolaita (33.1%) [10],Hawassa (48.8%) [17], Jimma (46.63%) [18], Daressalaam urban Tanzania (25.9%) [19], Kenya (0.2%) [20], and Nepal (9.1%) [21]. The difference might be due to geographical and socioeconomic variation because different areas may have difference in sanitation practice, warm and moist soils which facilitate the transmission and development of parasite ova and larva.…”
Section: Discussionmentioning
confidence: 62%
“…Hawassa [17], Jimma [18] and other countries Daressalaam urban Tanzania [19], Kenya (0.2%) [20], and Nepal (9.1%) [21].These differences in prevalence could be due to the use of different study subject, diagnostic methods and sociodemographic difference in the study subjects or due to a reflection of the local endemicity and geographic condition of the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The striking behavior found in agriculture in Vietnam is the use of wastewater and the use of human waste as fertilizer (Trang et al 2007). The prevalence of STH infections in adults, especially those working as farmers, has also been reported in Nepal, with very poor hygiene and sanitation patterns, including not using soap for handwashing and not using footwear when walking out of the house (Parajuli et al 2014). In contrary to the results of the study by Ross et al women were more at risk of STH infection than men, with the highest number of education being elementary and high schools.…”
Section: Resultsmentioning
confidence: 99%
“…Research reveals that not washing hands with soap is significantly associated with the prevalence and intensity of roundworm infections, hookworms and roundworms [16]. Dirty hands, dirty nails that allow worm eggs to slip, so they can be swallowed with food which can be aggravated by the habit of not washing hands before eating using soap and running water.…”
Section: A the Relationship Between Handwashing Behavior Before Eatimentioning
confidence: 99%
“…The research found that the habit of using footwear was related to helminthiasis [29]. Not wearing sandals or shoes is significantly associated with the prevalence and intensity of roundworm infections and hookworms, but not with the intensity of hookworm infection [16]. The use of footwear is very important to prevent the entry of worm larvae from the pores of the skin because if you often do not wear footwear it is at risk of infection with worms, if the infective form of larvae or worm eggs penetrates the outer skin through hair follicles, pores damaged skin and skin.…”
Section: Advances In Health Sciences Research Volume 18mentioning
confidence: 99%